EVALUATION OF PROGRAM BORDER MANAGEMENT TO KEEP SOVEREIGN NATION THE NORTH KALIMANTAN (Regional leadership Based on Transformational Leadership and lokal wisdom) - Dicky Wainal Usman; Djaali Djaali; R. Madhakomala R. Madhakomala (Program Studi S3 Ilmu Manajemen, 2017)
This research aimed to evaluate on five (5) steps;: (1) design of Border Management, (2) installation for Border Management,(3) process of Border Management, (4) product of Border Management, and cost / benefit for Border Management, for keep sovereignNation on North Kalimantan, This research is the programme evaluation research use Discrepancy Evaluation Model (DEM), data collection techniques are using; interview, observation, documentation and questionnaire for analyzer discussion support. Analysis of the data use Raph Tylor model as follows data reduction, data display and verification as conclusion.Results of this research include: (1) draft design, (2) border management plan, (3) compile of policy strategy with the help of stakeholders and HR agencies (4) the process of planning, organizing, staffing, directing, coordinating, reporting and budgeting for border management, and (5)lack of budget management.Besides is non-functioning of transformational leadership and effective local wisdom on North Kalimantan Keywords: Program Evaluation, Border Management, Regional Leadership, Transformational Leadership, Local Wisdom, Discrepancy Evaluation Model (DEM)